Feira de ciências : uma proposição metodológica para articular teoria-prática utilizando o diagrama V - Xavier, Lucas Antonio (2019)
This dissertation takes as reference a qualitative approach that aims to understand and describe meanings, which also adopts quantitative standards. A descriptive study about some experimental activities of Hydrostatic / Hydrodynamic and Electrodynamic for the Science Fair of the State School of Elementary and a history of 35 years of annual event. The activities developed were permeated by V Diagram Method, proposed by David Bob Gowin in 1977. To instill the method in the scientific event, Pedagogical Workshops were organized for the groups of students of the three series of High School. The proposal to use this heuristic instrument, due to its usability in the experimental context, is to promote the breaking of traditional itinerary practices. Two pedagogical workshops for regular high school students have been structured and offered with the objective of immersing these students in the new method. After the completion of the workshops, activities were carried out to promote greater familiarity with the new instrument. The researcher developed together with the groups of students eighteen experimental activities of Physics and were selected ten of them as object of this research: six groups were formed with students of the first year, one group with students of the second year and three groups with students of the third year. Seven activities about Fluids and three activities about Electrodynamics were carried out having the V Diagram as the north of the orientation procedures, data collection and evaluation throughout the process. The Vs diagrams produced by the groups of students were analyzed based on the criteria proposed by Novak and Gowin (1984) and Prado (2015) to establish the value criteria. In a general evaluation, it can be verified that the infusion of Gowin's heuristic was successful in propitiating the vision of thinking with praxis in the construction of knowledge. The educational product aimed to meet a demand of science education related to the organization of Science Fairs, through pedagogical workshops to promote the understanding of the scientific method through Diagram V. It can be inferred that these students began to perceive the importance of the dynamics of V Diagram as a referential instrument for the experiments developed for the Science Fair and for their explanation to the visiting public.